Endocytosis and intracellular trafficking of nanomaterials - Ferreira, L. A. B. (2015)
Recent advances in nanotechnology have increased the use of nanomaterials and nanodevices for diagnostic, therapeutic and other technological applications. The knowledge about the interaction between nanomaterials and biological media allows the development of more rational applications, as well understand and anticipate adverse and toxic effects resulting from this interaction. Endocytosis is an energy-dependent biological process responsible for internalization of nanoparticles, which depends on orchestrated events that require lipids and plasma membrane proteins functioning. Studies that aim to investigate in detail the endocytosis and intracellular trafficking of nanoparticles are essential for understanding cellular mechanisms, which in turn help to select its biomedical applications. In this context, this review aims to conceptualize the main routes of endocytosis used to study the internalization of nanomaterials in eukaryotic cells. In addition, we discuss some intracellular trafficking of nanomaterials to aid in studies of the cellular processing and development of new therapeutic tools.